Timing analysis of a sample of five cataclysmic variable candidates observed by the XMM–Newton satellite. Issue 1 (21st September 2022) - Nucita, A A; Lezzi, S M; De Paolis, F; Strafella, F; Licchelli, D; Franco, A; Maiorano, M
ABSTRACT: Intermediate polars are a class of cataclysmic variables in which a white dwarf accretes material from a companion star. The intermediate polar nature confirmation usually derives from the detection of two periods in both X -ray and optical photometry. In this respect, the high-energy signal is often characterized by modulations on the white dwarf spin and the orbital period. However, noting that the periodograms may be characterized by strong features also at the synodic period and/or other sidebands, the timing analysis of the X -ray signal may offer the unique possibility to firmly discover an intermediate polar candidate. Here, we concentrate on a sample of five cataclysmic variable binary candidates: i.e. SAXJ1748.2-2808, 1RXS J211336.1 + 542226, CXOGC J174622.7-285218, CXOGC J174517.4-290650, and V381 Vel, listed in the IPHome catalogue. Our main aim is to confirm if they belong to the intermediate polar class or not. The results of our analysis show that we can safely assess the intermediate polar nature of all the considered sources, apart for the case of V381 Vel which instead behaves like a cataclysmic variable of the polar subclass. Moreover, the source SAXJ1748.2-2808, previously classified as an HMXB, appears to be, most likely, an intermediate polar variable.